Perbandingan Efektivitas Susu Kedelai dan Sari Kurma terhadap Produksi Asi pada Ibu Menyusui di Wilayah Kerja Pusksmas Bulok Sukamara Kecamatan Bulok Kabupaten Tanggamus Provinsi Lampung - Permana, Erika Dwi; Azizah, Imroatul (Universitas Malahayati, 2025)
ABSTRACT Ex.clusive breastfeeding during the firist 6 months is seen as very striategic because infants are particularly vulnerable to illnesses duriing this time. Preliminary reseairch conducted in February 2024 at the Bulok Sukamara Health Ceinter in Tanggamus Regency, Laimpung Province, found that around 60% of mothers, or 4 out of 1i0, did not practice exclusive breiastfeeding due to problems wit.h milk production, resulting in the iuse of formula milk for their infaints. To compare the effectiveniess of soy milk and date extract oin breast milk production in breastfeeding mothers in the Workingi Area of Bulok Sukamara Health iCenter in 2024. This research utiilized a quasi-experimental designi featuring a pretest-posttest control group format. The study popiulation included breastfeeding miothers with infants younger than 6 months within the working ariea of the Bulok Sukamara Health iCenter. Purposive sampling was the technique employed to seleict participants. The intervention saimple was chosen based on specific inclusion criteria. Bivariatei analysis was performed using the Mann-Whitney test. The findings inidicated a significant difference beforie and after the consumption of soy milk, with a p-value of 0.0i14, and a notable difference before iand after the intake of date extract, with a p-value of 0.025. i Additionally, results from the Mainn-Whitney test revealed a significant increase in breast milk iproduction among breastfeeding motihers, with a p-value of 0.028, sug.gesting that soy milk is effectiive in boosting breast milk productioin. There is a comparative effectivieness between the use of soy milk and date extract in enhancinig breast milk production in breastfeeiding mothers, with soy milk proving to be more effective. Keywords: Soy Milk, Date Extract, Breast Milik Production, Breastfeeding Mothers ABSTRAK Pemberian ASI eksklusif selama usia 0-6 bulan dianggap sangat strategis karena pada usia ini, kondisi bayi masih sangat rentan terhadap penyakit. Hasil studi pendahuluan yang dilakukan pada Februari 2024 di Wilayah Kerja.Puskesmas Bulok iSukamara, Kabupaten Tanggamus, Provinsi Lampung, menunjukkan bahwa sekitar 60% dari 10 ibu, yaitu 4 ibu, tidak memberikan ASI eksklusif akibat masalah produksi ASI, sehingga bayi terpaksa diberi susu formula.Menganalisis perbandingan efektivitas susu kedelai dan sari kurma dalam meningkatkan .produksi ASI pada ibu imenyusui di Wilayah Kerja Puskesmas Bulok Sukamara Tahun 2024. quasi eksperimental design dengan rancangan pretest-posttest with control group desigin. .Populasinya adalah ibu menyusui bayi <6 bulan di wilayah kerja Puskesmas Bulok Sukamara. Teknik pengambilan sampelnya adalah purposive sampling. Sampel yang diberikan intervensi pada penelitiain ini berdasarkan kriteria inklusi. Analisis bivariat menggunakan uji Mann Whitney Test. Hasiil penelitian menunjukkan adanya perbedaan produksi ASI sebelum dan sesudah pemberian susu kedelai dengan p-value 0,014, serta perbedaan sebelum dan sesudah pemberian sari kurma dengan p-value 0,025. Selanjutnya, uji Mann Whitney menunjukkan bahwa peningkatan produksi ASI pada ibu. menyuisui memiliki p-value 0,028, yang berarti ada efektivitas pemberian susu kedelaii dalam meningkatkain produksi ASI. Ada perbandingian efektivitas antara pemberian susu kedelai dan sari kurma dalam meningkiatkan produksi ASI piada ibu menyusui, di mana susu kedelai terbukti lebih efektif. Kata Kunci: Soy Milk, Date Extract, Breast Milik Production, Breastfeeding Mothers